2023
DOI: 10.1101/2023.06.26.23291721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolome-wide Mendelian randomization characterizes heterogeneous and shared causal effects of metabolites on human health

Abstract: Metabolites are small molecules that are useful for estimating disease risk and elucidating disease biology. Nevertheless, their causal effects on human diseases have not been evaluated comprehensively. We performed two-sample Mendelian randomization to systematically infer the causal effects of 1,099 plasma metabolites measured in 6,136 Finnish men from the METSIM study on risk of 2,099 binary disease endpoints measured in 309,154 Finnish individuals from FinnGen. We identified evidence for 282 causal effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…Takebayashi et al demonstrated that the quenching of free radicals by ascorbic acid 2-sulfate was comparable to or greater than that of ascorbic acid over a prolonged period [52]. In the current study, it was found that ascorbic acid 2-sulfate has an impact on a wide range of diseases, including cardiomyopathy [53]. This compound may play a protective role in the kidneys of ACF rats.…”
Section: Discussionsupporting
confidence: 56%
“…Takebayashi et al demonstrated that the quenching of free radicals by ascorbic acid 2-sulfate was comparable to or greater than that of ascorbic acid over a prolonged period [52]. In the current study, it was found that ascorbic acid 2-sulfate has an impact on a wide range of diseases, including cardiomyopathy [53]. This compound may play a protective role in the kidneys of ACF rats.…”
Section: Discussionsupporting
confidence: 56%
“…The limited prediction of metabolite profiles may be related to the uncertain causal role in modulating T2D risk, a question investigated using Mendelian randomization (MR) 12 . One particular example is BCAAs, for which some studies have described a causal effect of valine, leucine and/or isoleucine on T2D [13][14][15] , while more recent evidence has shown no causal effect of BCAAs on T2D risk in the UK Biobank (UKBB) cohort 16 . Conversely, increasing evidence of a causal effect of T2D liability on metabolite profiles has been shown, with increased alanine levels caused by increased T2D liability being consistently reported 13,17,18 .…”
Section: Introductionmentioning
confidence: 99%